Long-term management of patients with epilepsy. Organization of a service in the Tyumen Region - E. V. Levitina; D. I. Lebedeva; O. A. Rakhmanina; K. V. Voronkova (Неврология, нейропсихиатрия, психосоматика, 2016)
Epilepsy is a chronic brain disease that requires a long-term or lifelong follow-up of patients. The factors that influence the outcome of therapy are various; moreover, the key factors of them are the organization of care and the mode of patient follow-up. The necessity of optimizing the specialized health care to this category of patients stems from the poorer quality of life in the patients and their families and from the more frequentdevelopment of mental disorders and drug-resistant forms of the disease during ineffective therapy. These and other issues are considered in this paper with emphasis on the specific area – the south of the Tyumen Region. This underlines the importance of setting up not only highlevel epileptologic centers, but also a whole network that provides access to specialized epileptologic care. It seems today that it is more appropriate to solve problems in the organization of management for epileptic patients at the level of an administrative region, for this state structure has all necessary conditions for rapidly and rationally implementing the most successful developments of specialized care to the population.